Analysis of Sexual Problems in Men With Psoriasis. Issue 8 (17th November 2018) - Wojciechowska-Zdrojowy, Marta; Reich, Adam; Szepietowski, Jacek C.; Wojciechowski, Adam
Abstract: Psoriasis may have a negative impact on many aspects of patient life. The aim of the study was to evaluate the influence of psoriasis on erectile dysfunction and other sexual problems in men with psoriasis. A total of 76 men aged between 20 and 66 years (mean 43.9 ± 13.2 years) were enrolled. Psoriasis severity assessed according to the Psoriasis Area and Severity Index (PASI) ranged from 2.0 to 49.8 points (mean 15.1 ± 10.3 points). All patients were asked to complete the International Index of Erectile Function, the Beck Depression Inventory (BDI), and the Dermatology Life Quality Index. A detailed medical history regarding sexual problems was also collected. Erectile dysfunction was found in 43.8% of patients. The severity of erectile dysfunction negatively correlated with the age of patients ( ρ  = –0.42; p <  0.01) and depressive symptoms assessed by BDI ( ρ  = –0.39, p <  0.01). The majority of patients (77.6%) declared that the skin condition at least occasionally negatively influenced their sexual life. Patients with more severe psoriasis more often avoided sexual intercourse ( p  < 0.01) and felt ashamed in front of their sexual partners ( p  = 0.04). The vast majority of men (96.1%) felt unattractive during psoriasis exacerbation and felt embarrassed if skin lesions were present on uncovered body regions. More than half avoided social activities and sexual intercourse due to psoriasis. Moreover, 44.7% experienced rejection during their life because of psoriasis. Psoriasis negatively influences mostly emotional aspects of sexual life. Psychological disturbances, severity of the disease, smoking, metabolic syndrome, and other concomitant diseases might influence the presence and progression of erectile dysfunction in psoriatic patients. Dermatologists should be aware of these problems to put more attention on this aspect of psoriasis.